High-wear-resistance rubber material and preparation method thereof
By mechanically blending the components such as white carbon black and polytetrafluoroethylene in fluorosilicone rubber, a three-dimensional network structure is formed, which solves the problem of insufficient wear resistance and strength of existing rubber materials, and achieves high wear resistance and high wear resistance Oil resistance and simplify the preparation process, suitable for aviation sealing.
Patent Information
- Application Number
- CN202411310873.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
The existing rubber materials have poor wear resistance and low strength, complex preparation process and high environmental pollution. Especially when the use of carbon black at high filler volumes leads to high processing difficulty and poor dispersion effect.
White carbon black is used as filler, and uniformly dispersed in fluorosilicone rubber through mechanical blending. Polytetrafluoroethylene and fluorinated graphene are added to form a three-dimensional network structure, and two-stage vulcanization is combined with a vulcanizing agent to improve wear resistance.
It realizes a rubber material with high wear and oil resistance, simplifies the preparation process, improves the mechanical properties and the feasibility of industrial production, and the material exhibits excellent performance at low and high temperatures.
Smart Images

Figure CN119192856A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber materials, and in particular relates to a highly wear-resistant rubber material and a preparation method thereof. Background Art
[0002] Rubber is an important part of the chemical industry. Rubber products such as tires, hoses, tapes, rubber rollers, rubber seals, and rubber tape products are widely used in various industries of the national economy, such as automobile production, aircraft manufacturing, crude oil transportation, electronic communications, and hospitals, and have become one of the important basic industries. At present, the basic raw materials of the rubber industry are natural rubber and synthetic rubber. Whether it is natural rubber obtained from nature or synthetic rubber obtained by humans through industrial means, although they have valuable high elasticity and a series of other excellent properties, they still have many shortcomings in performance. For example, the existing rubber materials have poor wear resistance and low strength, which results in poor use effect and short service life, and also increases the production cost of enterprises.
[0003] A Chinese patent with publication number CN107033466A and publication date 2017.08.11 discloses a high-strength wear-resistant rubber composite material, which is made of the following raw materials in parts by weight: 20-45 parts of polyurethane rubber, 10-20 parts of chloroprene rubber, 20-35 parts of ethylene propylene rubber, 10-23 parts of epichlorohydrin rubber, 8-18 parts of polychlorinated terphenyls, 8-16 parts of palm fiber, and 6-12 parts of polymerized iron phosphate powder. , 3-9 parts of nano silicon nitride, 2-7 parts of dimethyl carbonate, 1-6 parts of titanium nitride, 7-15 parts of micro powder silica gel, 5-10 parts of polyarylether nitrile, 6-14 parts of hard clay, 7-13 parts of graphite, 5-11 parts of calcium silicate, 2-6 parts of sulfur, 5-10 parts of petroleum phenyl sulfonate, 3-7 parts of nano alumina, 8-14 parts of polyamide fiber, 1.5-5 parts of antioxidant, 2-5 parts of antioxidant, 1-4 parts of accelerator. The rubber composite material has the following shortcomings: 1. The preparation process is cumbersome, and the required rubber matrix and reinforcing agent are more. In the preparation technology process, the rubber matrix is selected from a variety of types, the formula design is relatively complicated, the operation in the preparation process is complicated, and more than one reinforcing filler is used, such as palm fiber, polymerized iron phosphorus powder, nano silicon nitride, dimethyl carbonate, titanium nitride and hard clay, etc. There are relatively many variables in the formula design process, which is not easy to control. 2. The preparation takes a long time. After various reinforcing fillers are added, the mixing time takes 100 to 120 minutes. In addition, various processing aids and vulcanizers need to be added on this basis, which takes about 30 minutes. The preparation process is complicated.
[0004] A Chinese patent with publication number CN106566028A and publication date 2017.04.19 discloses a wear-resistant rubber, the raw materials of which include the following components by weight: 100 parts of raw rubber, 1-2 parts of zinc oxide, 3-10 parts of stearate, 1-3 parts of vulcanizing agent, 2-5 parts of accelerator, 50-100 parts of carbon black, 3-10 parts of magnesium oxide, 1-3 parts of antioxidant, 5-10 parts of zinc powder, 3-10 parts of magnesium methacrylate, 5-10 parts of oligoester, and 1-3 parts of coupling agent. The rubber material has the following deficiencies: 1. It has a large environmental pollution and a large amount of carbon black: In this preparation method, the required amount of carbon black is 50-100 parts, which is a large amount. The reinforcing effect is achieved by relying on the binding effect of carbon black on the rubber matrix. When the amount of carbon black used is large, the processing process is relatively complicated and the degree of environmental pollution is large. The in-situ blending method is used to prepare fumed silica reinforced fluorosilicone rubber, and polytetrafluoroethylene is used as a hybrid filler. During the preparation of the composite material, since fumed silica is added during the in-situ copolymerization to prepare fluorosilicone rubber, the environmental pollution is relatively small. At the same time, the use of polytetrafluoroethylene as a hybrid filler can further enhance the wear resistance of the material. 2. High processing difficulty and poor dispersion effect: When the carbon black filling amount is large, the dispersion of carbon black in the rubber matrix through mechanical blending has high requirements for operation. Mechanical blending makes it difficult to disperse the filler completely and evenly in the rubber matrix, and carbon black is prone to agglomeration in the rubber, resulting in stress concentration, thereby reducing the physical and mechanical properties of the material. Summary of the invention
[0005] In order to solve the problems of the above-mentioned prior art, a highly wear-resistant rubber material and a preparation method are proposed, white carbon black is used as a filler, and a mechanical blending method is used to achieve uniform dispersion of the reinforcing filler in the rubber matrix, polytetrafluoroethylene and fluorinated graphene are added to the rubber matrix to further improve the wear resistance of the rubber, and a wear-resistant and oil-resistant rubber sealing material is prepared. The material prepared by the present invention has a simple processing technology, is easy to industrialize, and has excellent mechanical properties.
[0006] The objective of the present invention is achieved through the following technical solutions: A highly wear-resistant rubber material comprises the following components in parts by weight: 100 parts of fluorosilicone rubber, 0.1-0.8 parts of a vulcanizing agent, 10-35 parts of a filler, 1-5 parts of polytetrafluoroethylene powder, 1-10 parts of fluorinated graphene, 1-2 parts of a heat-resistant agent, and 0.5-2 parts of a black dye.
[0007] Preferably, the molecular weight of the fluorosilicone rubber is ≥8*10 5 .
[0008] Preferably, the vulcanizing agent is a mixture of one or more of liquid dipentane, solid dipentane, dicumyl peroxide, benzamide peroxide, di-tert-butyl peroxide, and tert-butyl perbenzoate.
[0009] Preferably, the filler is a mixture of one or more of fumed silica and precipitated silica.
[0010] Preferably, the heat-resistant agent is a mixture of one or more of titanium dioxide, tin dioxide, iron oxide, copper oxide, nickel oxide, cobalt oxide, and chromium oxide.
[0011] Preferably, the dye is a carbon black dye.
[0012] A preparation method of a highly wear-resistant rubber material comprises the following steps: adding fluorosilicone rubber to an internal mixer for stirring, kneading for 5 minutes at room temperature, and setting the speed to 50 rpm; adding a filler to the internal mixer through a feeding port for mixing and stirring, kneading for 10 minutes at room temperature, and setting the speed to 50 rpm; adding polytetrafluoroethylene powder to the internal mixer for mixing and stirring, kneading for 5 minutes at room temperature, and setting the speed to 50 rpm; adding fluorinated graphene to the internal mixer for mixing and stirring, kneading for 5 minutes at room temperature, and setting the speed to 50 rpm; adding a heat-resistant agent to the internal mixer for mixing and stirring, kneading for 5 minutes at room temperature, and setting the speed to 50 rpm; adding a dye to the internal mixer for continuous mixing and stirring, kneading for 5 minutes at room temperature, and setting the speed to 50 rpm; subsequently, adding a vulcanizing agent to the internal mixer for mixing and stirring, kneading for 10 minutes at room temperature, and setting the speed to 50 rpm to obtain the mixed fluorosilicone rubber; finally, the mixed fluorosilicone rubber is thinly passed through a double-roll open mill to obtain the desired mixed rubber, and the mixed rubber is subjected to hot pressing and two-stage vulcanization to obtain a high wear-resistant rubber material.
[0013] Preferably, the rubber mix is thin-passed in a double-roll mill 8 to 12 times.
[0014] Preferably, the temperature during hot pressing of the rubber mix is 160-170° C., the pressure is 10-20 MPa, and the time is 10-20 min.
[0015] Preferably, the second-stage vulcanization temperature of the rubber mix is 200-250° C., and the second-stage vulcanization time is 2-4 h.
[0016] The beneficial effects of this technical solution are as follows: 1. The present invention provides a highly wear-resistant rubber material, which uses fluorosilicone rubber as a matrix, and respectively adds reinforcing fillers, polytetrafluoroethylene powder, fluorinated graphene, heat-resistant agent, dye and vulcanizing agent for internal mixing. A three-dimensional network structure is constructed between the reinforcing filler and the rubber matrix under the action of hydrogen bonds and van der Waals forces to achieve a reinforcing effect. Polytetrafluoroethylene has a low friction coefficient, good chemical resistance and high temperature stability, and can form a lubricating layer in the rubber to reduce the contact between the rubber and the friction surface and improve the wear resistance. Subsequently, the mixed rubber is thinly passed through a double-roll open mill for several times, and then hot-pressed and two-stage vulcanized to obtain the rubber material. The rubber material described in the present invention is prepared by the above method, and the preparation process is simple and can be industrialized. The prepared fluorosilicone rubber not only has excellent wear resistance and oil resistance, but also has excellent mechanical properties, high and low temperature resistance, etc.
[0017] 2. The present invention provides a method for preparing a highly wear-resistant rubber material. The uniform dispersion of reinforcing fillers in fluorosilicone rubber is achieved by mechanical blending. A three-dimensional network structure is constructed between the reinforcing fillers and the rubber matrix through hydrogen bonds and van der Waals interactions, achieving an excellent reinforcing effect. Polytetrafluoroethylene can form a lubricating layer in the rubber, reduce the contact between the rubber and the friction surface, and improve the wear resistance. The mechanical properties of the rubber material were tested according to the test method specified in GB / T528-2009. The tensile strength of the fluorosilicone rubber material was 9-11MPa, and the elongation at break was 500-700%. The mechanical properties test results were better than most silicone rubbers and fluorosilicone rubbers reported. The low-temperature brittle temperature of the rubber material was tested according to the test method specified in GB / T 1682-2014. The low-temperature brittle temperature of the fluorosilicone rubber material can reach -60°C. The friction coefficient of the fluorosilicone rubber material was tested by a friction and wear tester, and its friction coefficient was 0.27. The above results show that the wear-resistant and oil-resistant fluorosilicone rubber sealing material prepared by this method has excellent mechanical properties and wear resistance, and can be used in the field of aviation sealing. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 1 is the stress-strain curve of Example 1, Example 2, Example 3 and Example 4; Figure 2 is a curve showing the change of the friction coefficient over time in Example 1, Example 2, Example 3 and Example 4; Figure 3 This is a scanning electron microscope image of Example 3 after friction and wear. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0020] Example 1 100 parts by mass of fluorosilicone rubber was added to the internal mixer, stirred at 50 rpm for 5 min at room temperature, then 31 parts by mass of fumed silica was added, stirred at 50 rpm for 10 min at room temperature, then 1 part by mass of polytetrafluoroethylene powder was added and stirred at 50 rpm for 5 min, 2 parts by mass of fluorinated graphene were added and stirred at 50 rpm for 5 min, then 2 parts by mass of heat-resistant titanium dioxide was added and stirred at 50 rpm for 5 min at room temperature, then 1 part by mass of carbon black dye was added, and continued to stir at 50 rpm for 5 min at room temperature, then 0.53 parts by mass of liquid dipentadienyl vulcanizer was weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 min at room temperature. The compound was thinly passed 10 times in a double-roll open mill, and the compound was hot-pressed by a flat vulcanizer, with a hot-pressing temperature of 160 ° C, a hot-pressing time of 15 min, and a hot-pressing pressure of 10 MPa. Finally, the first-stage vulcanization sample was subjected to second-stage vulcanization in an oven. The second-stage vulcanization temperature was 200 °C and the vulcanization time was 4 h. After the second-stage vulcanization, a highly wear-resistant rubber material was obtained.
[0021] Example 2 100 parts by mass of fluorosilicone rubber was added to the internal mixer, stirred at 50 rpm for 5 min at room temperature, then 31 parts by mass of fumed silica was added, stirred at 50 rpm for 10 min at room temperature, then 2 parts by mass of polytetrafluoroethylene powder was added and stirred at 50 rpm for 5 min, then 3 parts by mass of fluorinated graphene was added and stirred at 50 rpm for 5 min, then 2 parts by mass of heat-resistant titanium dioxide was added and stirred at 50 rpm for 5 min at room temperature, then 1 part by mass of carbon black dye was added, and continued to stir at 50 rpm for 5 min at room temperature, then 0.53 parts by mass of liquid dipentadienyl vulcanizer was weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 min at room temperature. The compound rubber was thinly passed 10 times in a double-roll open mill, and the compound rubber was hot-pressed by a flat vulcanizer, with a hot-pressing temperature of 160 ° C, a hot-pressing time of 15 min, and a hot-pressing pressure of 10 MPa. Finally, the first-stage vulcanization sample was subjected to second-stage vulcanization in an oven. The second-stage vulcanization temperature was 200 °C and the vulcanization time was 4 h. After the second-stage vulcanization, a highly wear-resistant rubber material was obtained.
[0022] Example 3 100 parts by mass of fluorosilicone rubber was added to the internal mixer, stirred at 50 rpm for 5 min at room temperature, then 31 parts by mass of fumed silica was added, stirred at 50 rpm for 10 min at room temperature, then 3 parts by mass of polytetrafluoroethylene powder was added and stirred at 50 rpm for 5 min, then 5 parts by mass of fluorinated graphene was added and stirred at 50 rpm for 5 min, then 2 parts by mass of heat-resistant titanium dioxide was added, stirred at 50 rpm for 5 min at room temperature, then 1 part by mass of carbon black dye was added, and continued to stir at 50 rpm for 5 min at room temperature, then 0.53 parts by mass of liquid dipentadienyl vulcanizer was weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 min at room temperature. The compound was thinly passed 10 times in a double-roll open mill, and the compound was hot-pressed by a flat vulcanizer, with a hot-pressing temperature of 160 ° C, a hot-pressing time of 15 min, and a hot-pressing pressure of 10 MPa. Finally, the first-stage vulcanization sample was subjected to second-stage vulcanization in an oven. The second-stage vulcanization temperature was 200 °C and the vulcanization time was 4 h. After the second-stage vulcanization, a highly wear-resistant rubber material was obtained.
[0023] Example 4 100 parts by mass of fluorosilicone rubber was added to the internal mixer, stirred at 50 rpm for 5 min at room temperature, then 31 parts by mass of fumed silica was added, stirred at 50 rpm for 10 min at room temperature, then 5 parts by mass of polytetrafluoroethylene powder was added and stirred at 50 rpm for 5 min, 7 parts by mass of fluorinated graphene was added and stirred at 50 rpm for 5 min, then 2 parts by mass of heat-resistant titanium dioxide was added, stirred at 50 rpm for 5 min at room temperature, then 1 part by mass of carbon black dye was added, and continued to stir at 50 rpm for 5 min at room temperature, then 0.53 parts by mass of liquid dipentadienyl vulcanizer was weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 min at room temperature. The compound was thinly passed 10 times in a double-roll open mill, and the compound was hot-pressed by a flat vulcanizer, with a hot-pressing temperature of 160 ° C, a hot-pressing time of 15 min, and a hot-pressing pressure of 10 MPa. Finally, the first-stage vulcanization sample was subjected to second-stage vulcanization in an oven. The second-stage vulcanization temperature was 200 °C and the vulcanization time was 4 h. After the second-stage vulcanization, a highly wear-resistant rubber material was obtained.
[0024] Example 5 100 parts by mass of fluorosilicone rubber was added to the internal mixer, stirred at 50 rpm for 5 min at room temperature, then 20 parts by mass of precipitated silica was added, stirred at 50 rpm for 10 min at room temperature, then 3 parts by mass of polytetrafluoroethylene powder was added and stirred at 50 rpm for 5 min, then 2 parts by mass of fluorinated graphene was added and stirred at 50 rpm for 5 min, then 2 parts by mass of heat-resistant iron oxide was added and stirred at 50 rpm for 5 min at room temperature, then 1 part by mass of carbon black dye was added, and continued to stir at 50 rpm for 5 min at room temperature, then 0.53 parts by mass of di-tert-butyl peroxide vulcanizing agent was weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 min at room temperature. The compound rubber was thinly passed 10 times in a double-roll open mill, and the compound rubber was hot-pressed by a flat vulcanizer, with a hot-pressing temperature of 170 ° C, a hot-pressing time of 10 min, and a hot-pressing pressure of 15 MPa. Finally, the first-stage vulcanization sample was subjected to second-stage vulcanization in an oven. The second-stage vulcanization temperature was 230 °C and the vulcanization time was 3 h. After the second-stage vulcanization, a highly wear-resistant rubber material was obtained.
[0025] Example 6 100 parts by mass of fluorosilicone rubber was added to the internal mixer, stirred at 50 rpm for 5 min at room temperature, then 31 parts by mass of fumed silica was added, stirred at 50 rpm for 10 min at room temperature, then 1 part by mass of polytetrafluoroethylene powder was added and stirred at 50 rpm for 5 min, then 5 parts by mass of fluorinated graphene was added and stirred at 50 rpm for 5 min, then 2 parts by mass of heat-resistant titanium dioxide was added, stirred at 50 rpm for 5 min at room temperature, then 1 part by mass of carbon black dye was added, and continued to stir at 50 rpm for 5 min at room temperature, then 0.53 parts by mass of vulcanizing agent diisopropylbenzene peroxide was weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 min at room temperature. The compound rubber was thinly passed 10 times in a double-roll open mill, and the compound rubber was hot-pressed by a flat vulcanizer, with a hot-pressing temperature of 170 ° C, a hot-pressing time of 10 min, and a hot-pressing pressure of 15 MPa. Finally, the first-stage vulcanization sample was subjected to second-stage vulcanization in an oven. The second-stage vulcanization temperature was 200 °C and the vulcanization time was 4 h. After the second-stage vulcanization, a highly wear-resistant rubber material was obtained.
[0026] Example 7 100 parts by mass of fluorosilicone rubber was added to the internal mixer, stirred at 50 rpm for 5 min at room temperature, then 27 parts by mass of fumed silica was added, stirred at 50 rpm for 10 min at room temperature, then 2 parts by mass of polytetrafluoroethylene powder was added and stirred at 50 rpm for 5 min, then 3 parts by mass of fluorinated graphene was added and stirred at 50 rpm for 5 min, then 2 parts by mass of heat-resistant cobalt oxide was added and stirred at 50 rpm for 5 min at room temperature, then 1 part by mass of carbon black dye was added, and continued to stir at 50 rpm for 5 min at room temperature, then 0.53 parts by mass of vulcanizing agent di-tert-butyl peroxide was weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 min at room temperature. The compound was thinly passed 10 times in a double-roll open mill, and the compound was hot-pressed by a flat vulcanizer, with a hot-pressing temperature of 170 ° C, a hot-pressing time of 10 min, and a hot-pressing pressure of 20 MPa. Finally, the first-stage vulcanization sample was subjected to second-stage vulcanization in an oven. The second-stage vulcanization temperature was 200 °C and the vulcanization time was 4 h. After the second-stage vulcanization, a highly wear-resistant rubber material was obtained.
[0027] Example 8 100 parts by mass of fluorosilicone rubber was added to the internal mixer, stirred at 50 rpm for 5 min at room temperature, then 25 parts by mass of fumed silica was added, stirred at 50 rpm for 10 min at room temperature, then 5 parts by mass of polytetrafluoroethylene powder was added and stirred at 50 rpm for 5 min, 2 parts by mass of fluorinated graphene was added and stirred at 50 rpm for 5 min, then 2 parts by mass of heat-resistant nickel oxide was added and stirred at 50 rpm for 5 min at room temperature, then 1 part by mass of carbon black dye was added, and continued to stir at 50 rpm for 5 min at room temperature, then 0.8 parts by mass of vulcanizing agent diisopropylbenzene peroxide was weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 min at room temperature. The mixed rubber was thinly passed 10 times in a double-roll open mill, and the mixed rubber was hot-pressed by a flat vulcanizer, the hot pressing temperature was 170 ° C, the hot pressing time was 10 min, and the hot pressing pressure was 20 MPa. Finally, the first-stage vulcanization sample was subjected to second-stage vulcanization in an oven. The second-stage vulcanization temperature was 200 °C and the vulcanization time was 4 h. After the second-stage vulcanization, a highly wear-resistant rubber material was obtained.
[0028] Example 9 100 parts by mass of fluorosilicone rubber was added to the internal mixer, stirred at 50 rpm for 5 min at room temperature, then 31 parts by mass of precipitated silica was added, stirred at 50 rpm for 10 min at room temperature, then 3 parts by mass of polytetrafluoroethylene powder was added and stirred at 50 rpm for 5 min, then 5 parts by mass of fluorinated graphene was added and stirred at 50 rpm for 5 min, then 2 parts by mass of heat-resistant cobalt oxide was added and stirred at 50 rpm for 5 min at room temperature, then 1 part by mass of carbon black dye was added, and continued to stir at 50 rpm for 5 min at room temperature, then 0.6 parts by mass of vulcanizing agent tert-butyl peroxybenzoate was weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 min at room temperature. The mixed rubber was thinly passed 12 times in a double-roll open mill, and the mixed rubber was hot-pressed by a flat vulcanizer, with a hot-pressing temperature of 160 ° C, a hot-pressing time of 15 min, and a hot-pressing pressure of 15 MPa. Finally, the first-stage vulcanization sample was subjected to second-stage vulcanization in an oven. The second-stage vulcanization temperature was 200 °C and the vulcanization time was 4 h. After the second-stage vulcanization, a highly wear-resistant rubber material was obtained.
[0029] Example 10 100 parts by mass of fluorosilicone rubber was added to the internal mixer, stirred at 50 rpm for 5 min at room temperature, then 31 parts by mass of precipitated silica was added, stirred at 50 rpm for 10 min at room temperature, then 3 parts by mass of polytetrafluoroethylene powder was added and stirred at 50 rpm for 5 min, then 5 parts by mass of fluorinated graphene was added and stirred at 50 rpm for 5 min, then 2 parts by mass of heat-resistant agent tin dioxide was added, stirred at 50 rpm for 5 min at room temperature, then 1 part by mass of carbon black dye was added, and continued to stir at 50 rpm for 5 min at room temperature, then 0.6 parts by mass of vulcanizing agent tert-butyl peroxybenzoate was weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 min at room temperature. The compound rubber was thinly passed 12 times in a two-roll open mill, and the compound rubber was hot-pressed by a flat vulcanizer, with a hot-pressing temperature of 160 ° C, a hot-pressing time of 15 min, and a hot-pressing pressure of 15 MPa. Finally, the first-stage vulcanization sample was subjected to second-stage vulcanization in an oven. The second-stage vulcanization temperature was 230 °C and the vulcanization time was 3 h. After the second-stage vulcanization, a highly wear-resistant rubber material was obtained.
[0030] Embodiment 11 100 parts by mass of fluorosilicone rubber was added to the internal mixer, stirred at 50 rpm for 5 min at room temperature, then 31 parts by mass of precipitated silica was added, stirred at 50 rpm for 10 min at room temperature, then 3 parts by mass of polytetrafluoroethylene powder was added and stirred at 50 rpm for 5 min, then 5 parts by mass of fluorinated graphene was added and stirred at 50 rpm for 5 min, then 2 parts by mass of heat-resistant titanium dioxide was added, stirred at 50 rpm for 5 min at room temperature, then 1 part by mass of carbon black dye was added, and continued to stir at 50 rpm for 5 min at room temperature, then 0.6 parts by mass of vulcanizing agent diisopropylbenzene peroxide was weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 min at room temperature. The compound rubber was thinly passed 10 times in a double-roll open mill, and the compound rubber was hot-pressed by a flat vulcanizer, with a hot-pressing temperature of 170 ° C, a hot-pressing time of 10 min, and a hot-pressing pressure of 20 MPa. Finally, the first-stage vulcanization sample was subjected to a second-stage vulcanization in an oven. The second-stage vulcanization temperature was 230 °C and the vulcanization time was 3 h. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0031] Example 12 100 parts by mass of fluorosilicone rubber was added to an internal mixer, stirred at 50 rpm for 5 min at room temperature, then 10 parts by mass of precipitated silica and fumed silica were added, stirred at 50 rpm for 10 min at room temperature, 3 parts by mass of polytetrafluoroethylene powder were added and stirred at 50 rpm for 5 min, 1 part by mass of fluorinated graphene was added and stirred at 50 rpm for 5 min, then 1 part by mass of heat-resistant copper oxide and chromium oxide was added, stirred at 50 rpm for 5 min at room temperature, then 0.5 parts by mass of carbon black dye was added, and stirring was continued at 50 rpm for 5 min at room temperature, then 0.1 parts by mass of solid bis(25-pentyl)benzamide and peroxide of vulcanizing agent were weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 min at room temperature. The rubber mix was thinned 8 times in a two-roll open mill, and then hot-pressed in a flat vulcanizer at a temperature of 165°C, a time of 20 minutes, and a pressure of 20 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 250°C and a time of 2 hours. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0032] Example 13 100 parts by mass of fluorosilicone rubber was added to an internal mixer, stirred at 50 rpm for 5 min at room temperature, then 35 parts by mass of precipitated silica and fumed silica were added, stirred at 50 rpm for 10 min at room temperature, 5 parts by mass of polytetrafluoroethylene powder were added and stirred at 50 rpm for 5 min, 10 parts by mass of fluorinated graphene were added and stirred at 50 rpm for 5 min, then 1.5 parts by mass of heat-resistant copper oxide and chromium oxide were added, stirred at 50 rpm for 5 min at room temperature, then 2 parts by mass of carbon black dye were added, and stirring was continued at 50 rpm for 5 min at room temperature, then 0.1 parts by mass of solid bis(25-pentyl)sulfurizer and benzamide peroxide were weighed and slowly added to the fluorosilicone rubber, and stirred at 50 rpm for 10 min at room temperature. The rubber mix was thinned 8 times in a two-roll open mill, and then hot-pressed in a flat vulcanizer at a temperature of 165°C, a time of 20 minutes, and a pressure of 20 MPa. Finally, the first-stage vulcanized sample was subjected to a second-stage vulcanization in an oven at a temperature of 250°C and a time of 2 hours. After the second-stage vulcanization, a high-performance sealing rubber material was obtained.
[0033] The highly wear-resistant rubber materials obtained in Examples 1 to 4 were tested for mechanical properties according to the test method specified in GB / T 528-2009, the low-temperature brittle temperature of the rubber materials was tested according to the test method specified in GB / T 1682-2014, and the friction coefficient of the fluorosilicone rubber material was tested by a friction and wear testing machine.
[0034] The stress-strain curves of Example 1, Example 2, Example 3 and Example 4 are as follows: Figure 1 As shown, 1# represents the stress-strain curve of fluorosilicone rubber with 31 parts of fumed silica, liquid bis(2-5) as the vulcanizing agent, and 1 part by mass of polytetrafluoroethylene; 2# represents the stress-strain curve of fluorosilicone rubber with 27 parts of fumed silica, liquid bis(2-5) as the vulcanizing agent, and 2 parts by mass of polytetrafluoroethylene; 3# represents the stress-strain curve of fluorosilicone rubber with 31 parts of fumed silica, liquid bis(2-5) as the vulcanizing agent, and 3 parts by mass of polytetrafluoroethylene; 4# represents the stress-strain curve of fluorosilicone rubber with 31 parts of fumed silica, liquid bis(2-5) as the vulcanizing agent, and 5 parts by mass of polytetrafluoroethylene. Figure 1 It can be seen that the fluorosilicone rubber prepared by this method has excellent mechanical properties.
[0035] The curves of the friction coefficients of Example 1, Example 2, Example 3 and Example 4 changing with time are shown in FIG. Figure 2 As shown by Figure 2It can be seen that the friction coefficient of Example 3 is 0.27, and the rubber material has good wear resistance.
[0036] The scanning electron microscope image of Example 3 after friction and wear is as follows Figure 3 ,Depend on Figure 3 It can be seen that the material has good wear resistance.
[0037] Rubber products are used in various systems on aircraft. Their quality is directly related to the operation of the electrical, gas, oil and mechanical transmission systems on the aircraft, and is crucial to the safety, reliability and combat capability of the aircraft. Among them, rubber sealing materials are used in various parts of the aircraft, playing the role of sealing, shock absorption, heat insulation, fire prevention, transmission, support, etc., and are key materials necessary for the realization and guarantee of the functions of various aircraft systems. At the same time, some sealing rubbers come into dynamic contact with other structural parts during use, resulting in friction loss and failure. Therefore, improving the wear resistance of sealing rubber is extremely important for extending the service life and service reliability of sealing parts.
[0038] The rubber materials used in aircraft seals mainly include nitrile rubber, hydrogenated nitrile rubber, fluorine rubber, fluoroether rubber, silicone rubber, polysulfide rubber, polyurethane and EPDM rubber. Currently, nitrile rubber, which is widely used, is very easy to crack in the oil and gas environment, seriously affecting the service life and reliability of the aircraft. Many types of engines have serious consequences such as oil leakage due to the large changes in the cross-sectional dimensions of the nitrile rubber ring after oil resistance, and even cracking. Therefore, it is urgent to develop high-performance rubber sealing materials.
[0039] Fluorosilicone rubber is a type of polymer with a silicon-oxygen bond as the main chain and a fluorine-containing organic group replacing the side chain. It has the dual characteristics of organic silicon materials and organic fluorine materials. The introduction of fluorine atoms makes fluorosilicone rubber have excellent chemical stability, hydrophobicity, oil resistance and solvent resistance, etc. At the same time, it also has the excellent heat resistance, cold resistance, dielectricity, ozone resistance and aging resistance of silicone rubber. These excellent properties of fluorosilicone rubber make it widely used in aerospace, automotive industry and electronic products. At the same time, fluorosilicone rubber can usually be used in fuel media at a temperature of -68 to 230 ℃, but its mechanical properties are relatively poor like ordinary silicone rubber, the surface energy is relatively low, and the processing technology is relatively complicated. Therefore, studying reasonable formulas and processing technology to improve the performance of rubber is the most critical breakthrough point in the application of fluorosilicone rubber.
[0040] Finally, it should be noted that the above embodiments are only used to illustrate rather than limit the technical solutions of the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. Any modification or partial replacement that does not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A highly wear-resistant rubber material, characterized in that: The invention comprises the following components in parts by weight: 100 parts of fluorosilicone rubber, 0.1 to 0.8 parts of vulcanizing agent, 10 to 35 parts of filler, 1 to 5 parts of polytetrafluoroethylene powder, 1 to 10 parts of fluorinated graphene, 1 to 2 parts of heat-resistant agent and 0.5 to 2 parts of black dye.
2. A highly wear-resistant rubber material according to claim 1, characterized in that: The molecular weight of the fluorosilicone rubber is ≥8*10 5 .
3. The highly wear-resistant rubber material according to claim 1, characterized in that: The vulcanizing agent is a mixture of one or more of liquid dipentadienyl, solid dipentadienyl, dicumyl peroxide, benzamide peroxide, di-tert-butyl peroxide, and tert-butyl perbenzoate.
4. The highly wear-resistant rubber material according to claim 1, characterized in that: The filler is a mixture of one or more of fumed silica and precipitated silica.
5. The highly wear-resistant rubber material according to claim 1, characterized in that: The heat-resistant agent is a mixture of one or more of titanium dioxide, tin dioxide, iron oxide, copper oxide, nickel oxide, cobalt oxide, and chromium oxide.
6. The highly wear-resistant rubber material according to claim 1, characterized in that: The dye is a carbon black dye.
7. A method for preparing a highly wear-resistant rubber material, characterized in that: Fluorosilicone rubber is added to an internal mixer for stirring, and the internal mixing is performed at room temperature for 5 min, with the speed set to 50 rpm; filler is added to the internal mixer through the feeding port for mixing and stirring, and the mixing is performed at room temperature for 10 min, and the speed is set to 50 rpm; polytetrafluoroethylene powder is added to the internal mixer for mixing and stirring, and the mixing is performed at room temperature for 5 min, and the speed is set to 50 rpm; fluorinated graphene is added to the internal mixer for mixing and stirring, and the mixing is performed at room temperature for 5 min, and the speed is set to 50 rpm; heat-resistant agent is added to the internal mixer for mixing and stirring, and the mixing is performed at room temperature for 5 min, and the speed is set to 50 rpm; dye is added to the internal mixer for continuous mixing and stirring, and the mixing is performed at room temperature for 5 min, and the speed is set to 50 rpm; subsequently, vulcanizing agent is added to the internal mixer for mixing and stirring, and the mixing is performed at room temperature for 10 min, and the speed is set to 50 rpm to obtain the mixed fluorosilicone rubber; finally, the mixed fluorosilicone rubber is thinly passed through a double-roll open mill to obtain the desired mixed rubber, and the mixed rubber can be subjected to hot pressing and two-stage vulcanization to obtain a high wear-resistant rubber material.
8. The method for preparing a highly wear-resistant rubber material according to claim 7, characterized in that: The rubber mix is thinned in the double-roll mill 8 to 12 times.
9. The method for preparing a highly wear-resistant rubber material according to claim 8, characterized in that: The temperature of the rubber compound during hot pressing is 160-170° C., the pressure is 10-20 MPa, and the time is 10-20 min.
10. The method for preparing a highly wear-resistant rubber material according to claim 9, characterized in that: The second-stage vulcanization temperature of the rubber mix is 200-250°C, and the second-stage vulcanization time is 2-4 hours.
Citation Information
Patent Citations
Anti-wear rubber and preparation method thereof
CN106566028A
High-strength and wear-resistant rubber composite and preparation method thereof
CN107033466A
Cited By
A low-friction liquid silicone rubber composite and a method of making the same
CN122917543A
